Wise Acres : the seventh circle of Heck - Basye, Dale E. (Basye, Dale E. Circle of Heck, 2013)
"Milton and Marlo Fauster are sent to the circle of Heck for kids who sass back, where the new vice principal, Lewis Carroll, has them debate in a War of the Words broadcast throughout the underworld, with a reward of heaven for the winner and the ultimate punishment, the real h-e-double-hockeysticks, for the loser"--Provided by publisher.